Implementasi Pendidikan Karakter Berbasis Budaya Sekolah di SMP Negeri 1 Pabelan - Eminarni, Ferry Andika Eminarni; Murniati, Ngurah Ayu Nyoman; Abdullah, Ghufron (Media Manajemen Pendidikan, 2025)
Character education based on school culture is believed to have great potential in shaping students' positive character. Therefore, a clear description is needed in its implementation. This study aims to describe the implementation of character education based on school culture at SMP Negeri 1 Pabelan. This study uses a qualitative approach with a case study method. Data collection was carried out through observation, interviews, and documentation. The results of the study indicate that the planning of character education based on school culture at SMP Negeri 1 Pabelan is implemented through a special team (PPK team). The planning of priority character values is elaborated from the school's vision, mission, and goals. In 2025, it focuses more on critical, creative, and independent thinking. The implementation of Character Education uses a habituation model and role models in routine, spontaneous, and programmed activities. Character values are integrated into the learning process in the classroom. Co-curricular and extracurricular activities are explicitly designed to develop student character (especially activities related to local culture). Evaluation is carried out focusing on aspects of values, changes in student behavior, and teacher involvement. The evaluation results are analyzed and used as feedback for program improvement. The research recommendations are provided to schools to ensure they can sustainably maintain and strengthen positive values in character education. The Department of Education is expected to provide support for the development of character education resources.